Conformational Changes in a Macrolide Antibiotic Binding Protein From Mycobacterium smegmatis Upon ADP Binding - Zhang, Qingqing; Liu, Xiang; Liu, Huijuan; Zhang, Bingjie; Yang, Haitao; Mi, Kaixia; Guddat, Luke W.; Rao, Zihe (Frontiers in Microbiology, 2021)
Rv3197 (MABP-1), a non-canonical ABC protein in Mycobacterium tuberculosis, has ATPase activity and confers inducible resistance to the macrolide family of antibiotics. Here we have shown that MSMEG_1954, the homolog of Rv3197 in M. smegmatis, has a similar function of conferring macrolide resistance. Crystal structures of apo-MSMEG_1954 and MSMEG_1954 in complex with ADP have been determined. These structures show that MSMEG_1954 has at least two different conformations we identify as “inactive” and “active” forms. Structural superimposition shows that the “active” form of MSMEG_1954 has a similar conformation to that observed for MABP-1 and MABP-1-erythromicin complex structure. However, the antibiotic binding pocket in “inactive” form of MSMEG_1954 is completely blocked because of the location of the N-terminal accessory domain. When bound by ADP, the N-terminal accessory domain undergoes conformational change, which results in the formation of the antibiotic binding pocket.